Vascular progenitor cells and atherosclerosis. (November 2007) - Adams, Benjamin; Xiao, Qingzhong; Xu, Qingbo
Vascular regeneration occurs throughout life as a dynamic process. Millions of new endothelial cells are created with essentially the same number of cells undergoing programmed cell death or necrosis every day. As a result, the human vascular tree could be considered to essentially replace its entire endothelial population over a specified number of years. Within this network there is a compartment of vascular progenitor cells that appear to govern this homeostasis throughout life, continuously repopulating cells that die by apoptosis or necrosis. This delicate equilibrium appears to be disrupted in atherosclerotic disease processes as patients with known ischemic heart disease risk factors have been found to have lower numbers of circulating endothelial progenitor cells, which may tip the balance in favor of lesion formation, rather than repair. The aim of this article is to discuss the types of vascular progenitor cells and the mechanisms behind their mobilization, homing and differentiation into mature endothelial cells capable of vascular repair.